Membangun Pendidikan Karakter Berbasis Pendekatan Pragmatisme - Fatiya; Kholishah, Yunimar; Suhailah, Suhailah; Dila, Fitri Khairani; Arifi, Ahmad (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
Character education is an education that forms morals from within a person to have a good personality. In the formation of character education can be formed through a pragmatism approach. Where, in the pragmatism approach has the principle that real knowledge can be useful is useful for individuals. The purpose of this study is to find out Character Education in schools, find out Character Education in the pragmatism approach, and find out character education in learning. The research method used is a literature study. By collecting some relevant literature in the form of articles and online books. The results obtained that character education in schools has an important role in shaping students. The formation of Character Education through pragmatism is obtained by students through learning experiences at school which are not much different from learning experiences in life. Pragmatism in learning can be seen from the application of learning used which is practical and meaningful for everyday life.